Status of children born out of wedlock / Roslina Hashim - Hashim, Roslina (Faculty of Law, 1983)
The concept of legitimacy developed early to distinguish the offsprings of stable, permanent and recognised institution of marriage from those which are products of extra marital relationships with uncertain paternity. The legitimate offsprings enjoy the rights conferred upon them by law as a result of such status. The illegitimate ones, however, are discriminated just because of an accident of birth. The birth of an illegitimate child was regarded as bringing disgrace not only to the mother but also on her immediate family. The child could not be recognised as a real member of the family group. Chapter I of this paper provides a definition of legitimacy both under the common law and statute. It also gives a short discussion on the background of the attitude of the law towards legitimacy. Chapter II is concerned with the major areas of discrimination against the illegitimate children. It elaborates on the legal position of illegitimate children in relation to his right to maintenance, custody and guardianship and succession under the civil law. The current law is presented in considerable detail in this chapter. An account on whose surname the child is to bear, is also included under this chapter. Chapter III provides a general study on the existing laws of illegitimacy in England and the United States of America.